Maritime law - Hill, Christopher 1932- (Lloyd's practical shipping guides, 2003)
"The readable style and practical approach to the various objects discussed will recommend this book to a wide cross-section of readers involved in all aspects of the shipping industry, providing a comprehensive grounding on the general principles of maritime law for novices and acting as an invaluable guide to those already familiar with the complex intricacies of the subject."--BOOK JACKET